Comperation of Repelent Power of Orange Leaf Extract (Citrus Aurantifolia) and Nilam Leaf Extract (Pogostemon Cablin Benth) Toward Aedes Aegypti Mosquito - Ni Luh Ayu Meryanti; Nur Rismawati (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2022)
In this study, the research problems (1) How is the repulsion power of lime leaf extract (Citrus aurantifolia) and patchouli leaf (Pogostemon cablin benth) compared to Aedes aegypti mosquito?The objetives to be achieved ere (1) To find out the comparison of the repulsion power of lime leaf extract (Citrus aurantifolia) with patchouli leaf (Pogostemon cablin benth) against Aedes aegypti mosquitoes (2) To determine the repulsion power of lime leaf extract (Citrus aurantifolia) against Aedes aegypti mosquitoes (3) Knowing the effectiveness of patchouli leaf extract (Pogostemon cablin benth) toward Aedes aegypti Mosquito.